Review on efficiency and anomalies in stock markets - Kai-yin Woo; Chulin Mai; Michael McAleer; Wing Keung Wong (Economies, 2020)
The efficient-market hypothesis (EMH) is one of the most important economic and financial hypotheses that have been tested over the past century. Due to many abnormal phenomena and conflicting evidence, otherwise known as anomalies against EMH, some academics have questioned whether EMH is valid, and pointed out that the financial literature has substantial evidence of anomalies, so that many theories have been developed to explain some anomalies. To address the issue, this paper reviews the theory and literature on market efficiency and market anomalies. We give a brief review on market efficiency and clearly define the concept of market efficiency and the EMH. We discuss some efforts that challenge the EMH. We review different market anomalies and different theories of Behavioral Finance that could be used to explain such market anomalies. This review is useful to academics for developing cutting-edge treatments of financial theory that EMH, anomalies, and Behavioral Finance underlie. The review is also beneficial to investors for making choices of investment products and strategies that suit their risk preferences and behavioral traits predicted from behavioral models. Finally, when EMH, anomalies and Behavioral Finance are used to explain the impacts of investor behavior on stock price movements, it is invaluable to policy makers, when reviewing their policies, to avoid excessive fluctuations in stock markets.
Keywords: A10; G10; G14; O10; O16; 330; anchoring; anomalies; Behavioral Finance; behavioral models; BM effect; bubbles; calendar anomalies; causality; cointegration; copulas; covariance; Disposition Effect; diversification; dynamic models; EMH; Equity Premium Puzzle; herd effect; indifference curves; market efficiency; Momentum Effect; nonlinearity; ostrich effect; overconfidence; performance measures; portfolio optimization; portfolio selection; risk measures; robust estimation; stochastic dominance; technical analysis; the size effect; trading rules; two-moment decision models; unit root; utility; Winner-Loser Effect